INTERNALISASI NILAI MAJA LABO DAHU MELALUI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS TEKNOLOGI DIGITAL - Nur Hasanah (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2026)
Maja Labo Dahu, as a form of local wisdom of the Bima community, embodies the principles of ḥayā’ (modesty) and khauf (fear of Allah), which function as moral control in individual and social life. However, in the digital era characterized by the intensive use of technology, the internalization of these values among students tends to weaken. This article aims to describe the internalization of Maja Labo Dahu values through digital-based Islamic Religious Education (IRE) learning. This study employs a qualitative approach using library research methods and descriptive analysis of relevant literature on Maja Labo Dahu, Islamic moral education, and digital-based IRE learning. The findings indicate that the internalization of Maja Labo Dahu values can be implemented through the use of digital media, such as value-based instructional videos, interactive Islamic content, and online learning platforms that integrate local wisdom into the teaching of faith (ʿaqīdah), morals (akhlāq), and worship (ʿibādah). The internalization process occurs through stages of value understanding, habituation, and continuous reinforcement through reflective activities and self-evaluation. Digital-based IRE learning is able to enhance students’ moral awareness, religious attitudes, and character development when it is systematically and contextually designed. Therefore, integrating Maja Labo Dahu values into digital-based IRE learning constitutes an important strategy for strengthening character education grounded in local wisdom in the digital era.